2012
DOI: 10.4319/lo.2012.57.3.0711
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of ammonia oxidation rates and ammonia‐oxidizing archaea and bacteria at high resolution in the Gulf of California and eastern tropical North Pacific Ocean

Abstract: Ammonia-oxidizing microorganisms compete with phytoplankton for reduced nitrogen in the euphotic zone and provide oxidized nitrogen to other microbes present in the sea. We report 15 NH z 4 oxidation rate measurements made at 5-20-m resolution using an in situ array and quantification of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) in corresponding samples from the upper water column and oxygen minimum zone (OMZ) of the Gulf of California (GOC) and eastern tropical North Pacific Ocean (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(79 citation statements)
references
References 56 publications
10
68
0
1
Order By: Relevance
“…Depth-integrated nitrification rates were correlated with both depth-integrated Chl a (R 2 5 0.96) and sediment trap PON export at 60 m (R 2 5 0.94), the later reported by Munson et al (2015). Previous studies in the Pacific have found positive correlations between depth-integrated primary production and nitrification (Beman et al 2012;Shiozaki et al 2016). The correlations in our data and others support a direct and quantitative connection between nitrification rates, euphotic zone biomass, and PON export (Newell et al 2011).…”
Section: Discussionmentioning
confidence: 65%
“…Depth-integrated nitrification rates were correlated with both depth-integrated Chl a (R 2 5 0.96) and sediment trap PON export at 60 m (R 2 5 0.94), the later reported by Munson et al (2015). Previous studies in the Pacific have found positive correlations between depth-integrated primary production and nitrification (Beman et al 2012;Shiozaki et al 2016). The correlations in our data and others support a direct and quantitative connection between nitrification rates, euphotic zone biomass, and PON export (Newell et al 2011).…”
Section: Discussionmentioning
confidence: 65%
“…15 N-labeled ammonium ( 15 NH 4 Cl; Cambridge Isotope Laboratories) was added at a concentration of 50 nM (Santoro et al, 2010;Beman et al, 2012) to determine ammonia oxidation (AO) rates, and hydrogen peroxide (H 2 O 2 ; Fisher Scientific-Southern Ocean; J. T. Baker-GoM, GoA, Marsh Landing) was added to experimental treatments at target concentrations designated as either "low" (10-100 nM) or "high" (30-300 nM) amendments; actual H 2 O 2 additions varied by sample site ( Table 1, Supplementary Table 4). For these addition experiments, H 2 O 2 and 15 N-labeled ammonium were added directly to carboys for incubation; however, in the Southern Ocean 15 NH 4 Cl was added to duplicate, 250 mL subsamples after an initial incubation (6 h) with H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Catalase (Sigma Aldrich) was added to thawed samples (10 µL of 150 units L −1 catalase per 50 mL sample) that were incubated at room temperature for 60 min to prevent any inhibition of P. aureofaciens growth or denitrification ability by residual H 2 O 2 (no difference observed in N 2 O production with catalase addition; t-test, p = 0.43; Supplementary Table 5). AO rates were calculated from δ 15 N values as previously described (Christman et al, 2011;Beman et al, 2012); the detection limit for this measurement (0.001 nM d −1 ) was determined by using the detection limit for [NH 4 ] and [NO x ], as well as the uncertainty in stable isotope measurements with this setup (Beman et al, 2011).…”
Section: Ammonia Oxidation Rate Measurementsmentioning
confidence: 99%
“…It is possible that some of the relatively high variability in N 2 O produced per O 2 molecule consumed observed in Fig. 5 is due to mixing of water masses (Jin and Gruber, 2003), the variable abundance of bacterial and archaeal nitrifiers (Beman et al, 2012), or composition and availability of organic matter (Nevison et al, 2003). Also note that although we proxy N 2 O production via the N 2 O xs /AOU ratio, in reality the production would ideally be described by the relationship between N 2 O production and NH + 4 and NO − 3 loss, because the N 2 O xs /AOU ratio masks changes in the relative contribution of nitrification and denitrification at a given oxygen concentration.…”
Section: Calculating N 2 O Consumption Ratesmentioning
confidence: 99%
“…Archaea, for example, were only recently recognised as major contributors to nitrification (e.g., Beman et al, 2012) and marine N 2 O production (Santoro et al, 2011;Löscher et al, 2012). Information on their N 2 O production rates is still very limited.…”
Section: M Zamora Et Al: Nitrous Oxide Dynamics In Low Oxygen Rementioning
confidence: 99%